English Indonesian BilingualAttitudes Toward Codeswitching In Classroom Communication - Margana, Margana (Journal of English and Education (JEE), 2008)
This paper deals with the attitudes of English teachers and first grade students toward code-switching in classroom communication at junior high schools in Yogyakarta. It aims to describe their attitudes towards CS and to seek out practical implications for English language teaching and learning in Indonesia. To achieve the objectives, 240 first grade students and60English teachers from selected junior high schools volunteered to participate in this study. They were selected by a purposive sampling technique. Data was gathered thorough questionnaires and analyzed qualitatively and quantitatively using the statistical software of SPPS. The results revealed that(1)CS was positively perceived by participants, and(2) no significant difference in participant attitudes toward CS was found, in terms of gender, age, onset of English study, and teaching experience.